2019
DOI: 10.12968/johv.2019.7.5.226
|View full text |Cite
|
Sign up to set email alerts
|

Conversations with families about reducing the risk of sudden infant death syndrome

Abstract: Inequalities in the burden of sudden and unexpected deaths in infancy make targeted action by health professionals a viable option for intervention. Most of the deaths that now occur have at least one known modifiable risk factor present, so the potential impact of supporting families with implementing safer sleep strategies is great and may bring about a further reduction in infant deaths. This article describes the latest evidence for action on three of the major risk factors for SIDS: sleeping position; smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…With respect to content of risk reduction efforts, first asking families what they know of AAP recommendations can help identify potential gaps in knowledge and provide opportunity to share updated recommendations, or recent recalls or bans on products marketed for infant sleep. Second, structured, open‐ended, and non‐judgmental conversational approaches have been suggested to help identify risky practices or areas where families are struggling, and can obtain information on middle‐of‐the‐night practices 25–28 . For example, in this sample, several families described difficulties with getting infant to sleep on a recommended surface, excessive spitting up, and accidentally falling asleep when caring for infant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to content of risk reduction efforts, first asking families what they know of AAP recommendations can help identify potential gaps in knowledge and provide opportunity to share updated recommendations, or recent recalls or bans on products marketed for infant sleep. Second, structured, open‐ended, and non‐judgmental conversational approaches have been suggested to help identify risky practices or areas where families are struggling, and can obtain information on middle‐of‐the‐night practices 25–28 . For example, in this sample, several families described difficulties with getting infant to sleep on a recommended surface, excessive spitting up, and accidentally falling asleep when caring for infant.…”
Section: Discussionmentioning
confidence: 99%
“…Second, structured, open-ended, and non-judgmental conversational approaches have been suggested to help identify risky practices or areas where families are struggling, and can obtain information on middle-of-thenight practices. [25][26][27][28] For example, in this sample, several families described difficulties with getting infant to sleep on a recommended surface, excessive spitting up, and accidentally falling asleep when caring for infant. Third, inquiring about mother's/family's sleep and well-being can serve as an entry point for conversations about ways to address exhaustion-some mothers in this sample noted their sleep or comfort impacted their decision-making.…”
Section: Practice Implicationsmentioning
confidence: 99%
“…Applied to infant sleep practices, this approach acknowledges that parents make decisions about infant sleep practices based on what works within their familial and household context. Risk reduction around decisions to bed-share has been suggested by others [ 19 , 30 , 31 , 46 , 50 , 52 , 53 , 54 , 55 ]. Consistent with a risk reduction approach, coaches acknowledge the possibility of unplanned bed-sharing occurring [ 56 , 57 ] and plan with families how to reduce potential risk if it occurs [ 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…Our work with vulnerable families has shown that parents appreciate individually tailored advice that provides reasons, giving the how and why certain situations can increase risks for a baby. [28][29][30] The increased vulnerability exhibited among current SIDS deaths and continued exposure to several modifiable risk factors within the infant sleep environment despite widespread population-based risk reduction campaigns, suggest targeting resources to families most in need may reduce deaths further. Our specific recommendations based on these findings, are: 1.…”
Section: Recommendationsmentioning
confidence: 99%